2014
DOI: 10.1021/es503761j
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene Degradation Accelerated by Constructed Consortium of Bacterium and Microalga: Effects of Degradation Products on the Microalgal Growth

Abstract: Abundant microbes including bacteria, fungi, or algae are capable of biodegrading polycyclic hydrocarbons (PAHs). However, pure cultures never occur in the contaminated environments. This study aimed to understand the general potential mechanisms of interactions between microbes under pollution stress by constructing a consortium of PAH-degrading microalga (Selenastrum capricornutum) and bacterium (Mycobacterium sp. strain A1-PYR). Bacteria alone could grow on the pyrene, whereas the growth of algae alone was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…An algal–bacterial consortium consisting of Chlorella sorokiniana and Pseudomonas migulae was also reported for the degradation of phenanthrene under photosynthetic conditions and without an external source of oxygen (Munoz et al, 2003). In another study, accelerated pyrene degradation by a bacterial-algal consortium was reported under photosynthetic condition (Luo L. et al, 2014; Luo S. et al, 2014). These studies indicate that microalgae can be used singly or along with bacteria as a potential candidate for biodegradation of PAHs.…”
Section: Microalgal Degradation Of Pahsmentioning
confidence: 96%
See 1 more Smart Citation
“…An algal–bacterial consortium consisting of Chlorella sorokiniana and Pseudomonas migulae was also reported for the degradation of phenanthrene under photosynthetic conditions and without an external source of oxygen (Munoz et al, 2003). In another study, accelerated pyrene degradation by a bacterial-algal consortium was reported under photosynthetic condition (Luo L. et al, 2014; Luo S. et al, 2014). These studies indicate that microalgae can be used singly or along with bacteria as a potential candidate for biodegradation of PAHs.…”
Section: Microalgal Degradation Of Pahsmentioning
confidence: 96%
“…Removal and transformation of seven high molecular weight PAHs in water was reported by live and dead cells of a freshwater microalga, Selenastrum capricornutum under gold and white light irradiation. The removal efficiency of PAHs, and the effectiveness of live and dead cells, was found to be predominantly PAH dependent (Ke et al, 2010; Luo L. et al, 2014; Luo S. et al, 2014). The first study on the potential of algal–bacterial microcosms was reported for the biodegradation of aromatic pollutants comprising salicylate, phenol and phenanthrene in a one-stage treatment (Borde et al, 2003).…”
Section: Microalgal Degradation Of Pahsmentioning
confidence: 99%
“…established a consortium consisting of microalgae ( Selenastrum capricornutum ) and a bacterium ( Mycobacterium sp. strain A1‐PYR) that achieved faster degradation of pyrene than the systems that used algae or bacteria alone (Luo et al ., ). The same result was obtained by a synthetic consortium combining Synechocystis sp.…”
Section: Algae–bacteria‐based Wastewater Treatmentmentioning
confidence: 97%
“…Algal cells not only provide stable habitats for the bacteria but also concentrate pollutants to enhance bioavailability for bacterial degradation (Gutierrez et al, 2014). Algal-bacterial consortia successfully achieved higher biodegradation or removal rates of pollutants than single species (Luo et al, 2014).…”
Section: Removal Of Heavy Metals and Toxic Organic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation